2015
DOI: 10.1021/acs.biochem.5b00324
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Perturbations of Binuclear Non-heme Iron Sites: Structure and Dioxygen Reactivity of de Novo Due Ferri Proteins

Abstract: DFsc (single-chain due ferri) proteins allow for modeling binuclear non-heme iron enzymes with a similar fold. Three 4A → 4G variants of DFsc were studied to investigate the effects of (1) increasing the size of the substrate/solvent access channel (G4DFsc), (2) including an additional His residue in the first coordination sphere along with three additional helix-stabilizing mutations [3His-G4DFsc(Mut3)], and (3) the three helix-stabilizing mutations alone [G4DFsc-(Mut3)] on the biferrous structures and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 60 publications
(173 reference statements)
1
52
0
Order By: Relevance
“…This is confirmed where the rate of the O 2 reaction for G4DFsc+P-AN is 0.002 s −1 (Figure S14) (relative to ~0.02 s −1 without p -anisidine). 52 In contrast, the binding of p -anisidine to the 3His form results in only a small change in exchange-coupling (− J from 1–2 cm −1 to 2–3 cm −1 ), and the rate of obtaining steady state for nitroso production ( k ≈ 0.045 s −1 , Figure S15) is close to the O 2 reaction rate of the 3His form without substrate (~0.04 s −1 ). 52 …”
Section: Results and Analysismentioning
confidence: 91%
See 4 more Smart Citations
“…This is confirmed where the rate of the O 2 reaction for G4DFsc+P-AN is 0.002 s −1 (Figure S14) (relative to ~0.02 s −1 without p -anisidine). 52 In contrast, the binding of p -anisidine to the 3His form results in only a small change in exchange-coupling (− J from 1–2 cm −1 to 2–3 cm −1 ), and the rate of obtaining steady state for nitroso production ( k ≈ 0.045 s −1 , Figure S15) is close to the O 2 reaction rate of the 3His form without substrate (~0.04 s −1 ). 52 …”
Section: Results and Analysismentioning
confidence: 91%
“…52 However, 3His-G4DFsc(Mut3) only formed the biferric paramagnetic species B due to the additional His coordinatively saturating one iron center. In our prior studies that showed oxidase reactivity for G4DFsc, but not for the 3His form, Fe(II) was added under aerobic conditions to a solution of apo-protein and 4-AP ( 1 ) in the presence of m -phenylenediamine ( 3 ), which couples to the oxidized product (quinone imine) ( 2 ) to yield an aminoindoaniline dye ( 4 ) with λ max = 486 nm ( ε = 13 200 cm −1 M −1 ) at pH 7 (Figure 2).…”
Section: Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations